1998
DOI: 10.1144/gsl.sp.1998.134.01.12
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal shortening control of Middle Miocene marine siliciclastic accumulation (Upper Marine Molasse) in the southern termination of the Savoy Molasse Basin (northwestern Alps/southern Jura)

Abstract: Between the southern Jura and the Subalpine Chains (Bornes, Bauges, and Chartreuse Massifs), the Burdigalian-Langhian-Serravalian tidal siliciclastic 'Upper Marine Molasse' (UMM) outcrops in N-S synclines between N-S-trending ramp anticlines separating southward-narrowing synclines. A surface survey and an interpretation of transverse seismic-reflection profiles across the latter confirm that they represent progressively individualized and separated sedimentation areas. Combined seismic configuration and surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 13 publications
3
31
0
Order By: Relevance
“…With regard to the timing of Jura deformations, Deville et al (1994) andbeck et al (1998) have shown that deformations were initiated 15 Ma ago in the innermost part of the southern Jura (Montagne d'Age, Mandallaz and salève anticlines, Fig. 1).…”
Section: Geochronological Datamentioning
confidence: 99%
“…With regard to the timing of Jura deformations, Deville et al (1994) andbeck et al (1998) have shown that deformations were initiated 15 Ma ago in the innermost part of the southern Jura (Montagne d'Age, Mandallaz and salève anticlines, Fig. 1).…”
Section: Geochronological Datamentioning
confidence: 99%
“…Starting in Campanian times, compressional stresses were exerted on the West Alpine passive margin in conjunction with convergence of the Apulian block with the continental Briançonnais terrain and the early phases of the Pyrenean orogeny (Roure and Colletta, 1996;Stampfli et al, 1998;Philippe et al, 1998). During the Paleocene, this margin was uplifted, as evidenced by the development of a regional unconformity Beck et al, 1998); this was accompanied by upthrusting of a basement block in the Pelvoux Massif (Ford, 1996). Although interpreted as reflecting the development of a flexural forebulge (Crampton and Allan, 1995), this deformation was more likely controlled by a combination of compressional stresses transmitted into the foreland crust from the Alpine collision front through the oceanic crust of the Valais Trough and from the Pyrenean orogen.…”
Section: West Alpine Forelandmentioning
confidence: 99%
“…22) (Schmid and Kissling, 2000). By this process, the earlier formed flexural foreland basin was largely destroyed (Roure and Colletta, 1996;Ziegler and Roure, 1996;Beck et al, 1998;Lickorish and Ford, 1998). Moreover, these foreland stresses impeded the evolution of the Cenozoic rift system (Ziegler, 1994;Sissingh, 2001).…”
Section: West Alpine Forelandmentioning
confidence: 99%
“…With these, it is possible to obtain information that may include the dip of basal décollements, the shape of the topographic surface, and the structural geometry of the orogenic wedge (Meigs and Burbank, 1997;Ford, 2004), allowing inferences to be made about the geometric, kinematic, and mechanical evolution of external orogenic belts (see Meigs et al, 1996;Meigs, 1997;Ford, 2004). Relevant examples of such analyses include the southcentral Pyrenees (Burbank and Puigdefàbregas, 1992;Arbués et al, 1996;Martínez Rius et al, 1996;Meigs et al, 1996;Meigs, 1997;Meigs and Burbank, 1997;Nijman, 1998), the Sevier thrust belt DeCelles, 1988;Lawton and Trexler, 1991;DeCelles et al, 1995;Talling et al, 1995;Mitra and Sussman, 1997;DeCelles and Coogan, 2006), the Northern Apennines (Doglioni and Prosser, 1997;Ford, 2004), the subalpine chains of the external western Alps (Artoni and Meckel, 1998;Beck et al, 1998;Lickorish and Ford, 1998;Evans and Elliot, 1999), the Seram Trough in Indonesia (Pairault et al, 2003), NW Borneo (Ingram et al, 2004), and the Makran accretionary prism (Grando and McClay, 2007).…”
Section: Introductionmentioning
confidence: 99%